PEMANFAATAN LIMBAH TEMPURUNG KELAPA SEBAGAI CAMPURAN PAVING BLOCK (Ditinjau dari Kuat Tekan dan Resapan Air) - Ilham Adji Sucahyo; Hammam Rofiqi Agustapraja; Bobby Damara (Kadiri University, 2020)
The main objective of this study was to find out and analyze how much the influence of the coconut shell charcoal had on changes in compressive strength and water absorption in the K-175 paving block. This research method is experimental research, which is a research of making paving block specimens, by conducting activities or experiments using coconut shell waste as a mixture of paving blocks, with a mix design mix referring to the comparison of concrete mix with K-175 quality (SNI 03-2834-2000). The conversion value of compressive strength of specimens at the age of 7 days to 28 days from specimens N, 5%, 10%, 15% and 20% is 271,80 kg/cm², 205,12 kg/cm², 102,57 kg/cm²,76,92 kg/cm² and 64,11 kg/cm² respectively. In the normal test code, the paving block is classified as class B quality, while the 5% specimen code is classified as class B quality, for the test object code 10%, 15%, and 20% do not meet the paving block quality standards. The results of the water absorption test increased in paving blocks with a combination of coconut shell charcoal. All of them have increased water infiltration on paving blocks.Tujuan utama dari penelitian ini adalah untuk mengetahui dan menganalisa seberapa besar pengaruh arang tempurung kelapa terhadap perubahan kuat tekan dan resapan air pada paving block K-175. Metode penelitian ini adalah penelitian eksperimen, yaitu penelitian pembuatan benda uji paving block, dengan cara melakukan kegiatan atau percobaan pemanfaatan limbah tempurung kelapa sebagai campuran paving block, dengan perbandingan mix design mengacu pada perbandingan campuran beton dengan mutu K-175 (SNI 03-2834-2000). Hasil nilai konversi kuat tekan benda uji pada umur 7 hari ke umur 28 hari dari benda uji N, 5%, 10%, 15%, dan 20% adalah 271,80 kg/cm², 205,12 kg/cm², 102,57 kg/cm²,76,92 kg/cm² dan 64,11 kg/cm². Pada kode benda uji normal paving block tergolong dalam mutu kelas B, sedangkan pada kode benda uji 5% tergolong dalam mutu kelas B, untuk kode benda uji 10%, 15%, dan 20% tidak memenuhi standar mutu paving block. Hasil dari uji resapan air paving block dengan penambahan arang tempurung kelapa dari benda uji 5%, 10%, 15% dan 20%. Kesemuanya mengalami peningkatan resapan air pada paving block.